PERAN INFAQ DAN SEDEKAH DALAM PEMERDAYAAN EKONOMI UMAT DI ERA DIGITAL - Rossella Afriani; Fatimah Yunus; Gustiya Sunarti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This research is a study using the literature study method or literature review to show readers about “The role of infaq and alms in the economic empowerment of the people in the digital era” and examine data from various literatures related to the core of the problem in order to obtain the principles and concepts about the problem that is the object of research. The method used in this article is descriptive method, various forms of information and references related to the issue of managing infaq and alms in the digital era.  The results of the study show that amil are required to have modern skills in collecting funds. Digitalization of infaq and sadaqah fund collection is digital payment and digital socialization by utilizing social media. Digitalization in collecting infaq and sadaqah funds plays a role because it makes it easier for muzakki to save time and money. And also makes fundraising more transparent, massive, effective and efficient. However, the role of digitalization has not been maximized due to the lack of human resources and the lack of a digital system that is very minimal and people who are not yet literate in digital technology.